American popular song the great innovators, 1900-1950 - Wilder, Alec 1907-1980; Rawlins, Robert ca. 20./21. Jh (Oxford scholarship online, 2022)
Composer Alec Wilder's 'American Popular Song' is widely recognized as the definitive book on American popular song. In this volume, which achieved immediate praise and recognition upon its publication, Wilder discusses some 800 songs from the American Songbook, offering a composer's insight, accessible music analysis, as well has his strong personal biases. Nearly 50 years later, this classic study has received a much-needed revision. While leaving Wilder's colorful prose and brazen opinions intact, language, style, and musical nomenclature have been updated to reflect current usage. The musical examples mostly remain, but piano score notation has been replaced with lead-sheet notation: melody, chords, and lyrics. Rhythmic notation has also been adjusted to follow present-day norms. Additionally, a final chapter has been added, which includes more than 50 songs that were not in the original.